Toxic Effects of Profenofos Based Insecticide on Freshwater Fish Mozambique Tilapia (Oreochromis mossambicus) - Pawar , Rachna Shrivastava; Shrivastava, Pragya (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
This study was performed to investigate the toxic effects that associated with experimental exposure of mossambique tilapia to Profenofos based insecticide containing Profenofos 40% + Cypermethrin 4%. 96 hours exposures to 2.0068 µL/ L and 2.80952 µL/ L doses were conducted to evaluate the toxic effects, and various toxicological endpoints were assessed. Acute toxic stress was observed with fish displaying behavioral toxicity. Histopathological alterations in the liver, kidney, and brain occurred exclusively after treatment. The Histopathological effects of Profenofos based pesticide on the liver, kidney and brain tissues in Oreochromis mossambicus were determined by light microscopy. The fish were exposed to different concentrations of Profenofos based insecticide for 96 hours with parallel untreated control. No Histopathological effects were observed in control group. dilation of Bowman’s space, G: deterioration of glomerulus, RT: increase in diameter of renal tubule, CD: cellular degeneration. Cellular degenerative processes can result in tissue necrosis in very severe scenarios. Collapse of glomeruli and blood hemorrhage and can lead to rise in the level of edematous fluid within interstitial substance were observed in kidney tissues exposed to Profenofos based insecticide Hepatic lesions in the liver tissues of fish exposed to profenofos based insecticide were characterized by cytoplasmic vacuolation, cellular degeneration, damage of nuclei, bile stagnation as well as clogging in the blood sinusoids. Pesticides have the potentials of causing an increase or decrease of enzymatic processes and as such result in histological alterations. Noticeable alterations in Stratum opticum, Stratum fibrosum and griseum superficial, Stratum griseum central, Stratum album central and Stratum griseum periventricular. This study has shown that increase in concentration of pesticide with treated produced water resulted in degeneration and damage brain cells as well as clogging in the blood sinusoids. Pesticides have the potentials of causing an increase or decrease of enzymatic processes and as such result in histological alterations. From the obtained results, it is assumed that Profenofos induced general toxic impacts.